Transparent lithium aluminosilicate glass ceramics

By optimizing the proportion of ingredients such as SIO2, Al2O3 and LI2O, and adding ingredients such as Zno, BAO, and ZRO2 to adjust the thermal expansion coefficient, light transmission and color of transparent lithium aluminum silicate glass ceramics, solve the lithium content in the existing technology The problem of melting characteristics and cost benefits caused by reducing the glass ceramics with lower cost and lower color perception of distortion.

CN119330598APending Publication Date: 2025-01-21SCHOTT AG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410971776.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the case of reducing the lithium content, existing transparent lithium aluminosilicate glass ceramics are difficult to maintain good melting characteristics and cost-effectiveness of green glass, and there is also the problem of color perception distortion.

Method used

Through the optimized ingredient ratio, the specifically SiO2 62–68WT %, Al2O3 19–24WT % and LI2O 2.4–3.1WT %, combined with ZNO, BAO and ZRO2, regulate the thermal expansion coefficient, light transmission rate and chroma of glass ceramics to ensure The thermal expansion coefficient in the range of 20 ° C to 700 ° C is between -0.8 and 1.5 ppm/k.

Benefits of technology

In the case of reducing the lithium content, maintain the good melting characteristics and cost benefits of glass ceramics, while reducing the distortion of color perception, and suitable for cooking surfaces of various heating elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004953443640000031
    Figure BDA0004953443640000031
  • Figure BDA0004953443640000041
    Figure BDA0004953443640000041
  • Figure BDA0004953443640000111
    Figure BDA0004953443640000111
Patent Text Reader

Abstract

The invention relates to a transparent lithium aluminosilicate glass ceramic and to the use of the transparent lithium aluminosilicate glass ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to transparent lithium aluminosilicate glass ceramics which are particularly suitable for use as cooking surfaces for cookware and to their use. Background Art

[0002] Glass ceramics, in particular transparent glass ceramics, have been known for many years. A variant of such glass ceramics known in the prior art is lithium aluminum silicate (LAS) glass ceramics, which have high quartz mixed crystals (HQMK) (in particular for transparent materials) or keatnetite mixed crystals (KMK) (in particular for translucent or opaque materials) as the main crystalline phase. In order to produce such glass ceramics, an initial glass, the so-called green glass, is first produced using a process that is relatively common in glass manufacturing. These green glasses are converted into glass ceramics by heat treatment (ceramicization). The transparent glass ceramics produced in this way can be used in different fields. In particular, such glass ceramics are used as cooking surfaces. In addition, such glass ceramics are also used as viewing windows for stoves and ovens, as worktops or safety glass.

[0003] The essential property of these materials for use as cooking surfaces is that they have a very low thermal expansion in the temperature range from room temperature to 700° C. This low thermal expansion in turn leads to a high resistance to temperature changes. The thermal expansion is adjusted by combining a crystalline phase with negative thermal expansion with an amorphous residual glass phase with positive thermal expansion. In the glass ceramics used to date, lithium oxide contents of more than 3.6 to 5.0 wt. % are usually used for this purpose.

[0004] Due to the rising raw material price of lithium, it is advantageous for economic reasons to reduce the lithium content in glass ceramics to a minimum. However, lithium is one of the three main components of lithium aluminosilicate glass ceramics and cannot be reduced at will. 2 The O content directly affects the core properties of the glass ceramic, such as viscosity in the melt and hot forming, which is important for manufacturability, or thermal expansion, which is important for use as a cooking surface.

[0005] Lithium price trends are not a new issue. Over the past 20 years, lithium prices have continued to rise. Despite this long-standing need, most commercially available glass-ceramics for cooking surfaces have about 3.8 wt% Li or more. 2 O.

[0006] The following documents reveal Li 2Glass ceramics with an O content of less than 3.5 wt%: WO 2012 / 010341 A1, EP3502069A1, US2017050880, US2020189965, US2020140322, US2021387899, WO2021 / 224412A1. However, these glass ceramics have different disadvantages, such as reduced resistance to temperature changes or poor solubility of green glass.

[0007] The applicant describes, for example, in DE 20 2022 106 826 U1 that even Li 2 Basic methods for producing lithium aluminosilicate glass-ceramics with low O contents are described, which avoid the above-mentioned disadvantages. 2 A method for producing transparent glass-ceramics with low O content.

[0008] In addition to the above-mentioned temperature stability, there are other special requirements for transparent glass ceramics. When using transparent glass ceramics as cooking surfaces, they are usually provided with a colored bottom coating so that the heating elements and the associated electronics arranged below the glass ceramic cannot be seen from above. In this case, it is usually required that the color perception of this bottom coating by the end user is not distorted by the glass ceramic. Similar requirements are imposed on the glass ceramic when using transparent glass ceramics as viewing windows, because in this case, color distortion must also be avoided when viewing through the viewing window.

[0009] Here, transparent glass ceramics generally refer to glass ceramics with low light scattering. The transmittance of such transparent glass ceramics can be adjusted within a wide range by means of absorption components (ie, coloring components). Summary of the invention

[0010] The object of the present invention is to provide a transparent lithium aluminum silicate glass ceramic which has good green glass melting properties and is relatively low in cost, but does not limit its performance in use. In addition, the glass ceramic according to the present invention should minimize the distortion of color perception caused by the glass ceramic.

[0011] In this case, good melting properties are manifested in a processing point temperature of at most 1340° C., preferably below 1330° C., particularly preferably below 1320° C. This processing point is a viscosity of the green glass of 10 4 dPa*s. The hot forming of green glass is carried out near this temperature. The higher the temperature during hot forming, the more complicated it is to dissipate the heat introduced into the forming machine through the glass. When the temperature exceeds 1340°C, the heat can only be reduced by reducing the production of glass. However, this is economically disadvantageous.

[0012] During hot forming, if the temperature is below the so-called devitrification upper temperature, undesirable spontaneous crystallization (also called "devitrification") may occur. In order to prevent the above situation, it is advantageous that the devitrification upper temperature is at least 10K lower than the processing point, preferably at least 15K lower, particularly preferably at least 20K lower, and especially preferably at least 30K lower.

[0013] In particular, the glass ceramic should meet all requirements for use as a cooking surface with various heating elements. These include, in particular, radiation heating elements, induction heating elements and gas heating elements. This requires, in particular, a sufficiently high resistance to temperature changes and a high long-term heat resistance.

[0014] The solution of the present invention for achieving the above-mentioned object lies in the subject matter of the independent claim. Preferred embodiments and improved solutions are shown in the dependent claims.

[0015] The transparent lithium aluminum silicate glass ceramic according to the present invention has a thermal expansion coefficient of -0.8 to 1.5 ppm / K in the range of 20° C. to 700° C., and a light transmittance τ of the transparent lithium aluminum silicate glass ceramic based on a thickness of 4 mm. vis More than 75%, and based on a thickness of 4 mm, its chromaticity C* is less than 10. In this case, the glass ceramic contains the following components in the given contents (based on oxides, in wt %):

[0016]

[0017] Glass ceramics with a corresponding coefficient of thermal expansion have both a high resistance to temperature changes and a high long-term thermal stability. They are therefore suitable for use as cooking surfaces with various heating elements. The coefficient of expansion is at least -0.8 ppm / K. In this context, "ppm" means "parts per million", i.e. a relative dimensional change of 10 for a temperature change of 1 K. -6 Negative thermal expansion values ​​should be avoided. In the case of negative expansion (i.e. contraction), tensile stresses can develop in the surface of the glass ceramic during heating. At values ​​below -0.8 ppm / K, these stresses can reduce the mechanical strength of the cooking surface at the usual operating temperatures of the cooker. Thermal expansion rates of more than 1.5 ppm / K should also be avoided. Expansion rates of more than 1.5 ppm / K do not ensure that the glass ceramic has a sufficiently high resistance to temperature changes for use in cookers with radiant heating elements.

[0018] In one embodiment of the invention, the thermal expansion coefficient is at least -0.6 ppm / K, -0.4 ppm / K, -0.2 ppm / K, 0.0 ppm / K, 0.2 ppm / K, 0.4 ppm / K, 0.6 ppm / K or even 0.8 ppm / K. Furthermore, the thermal expansion coefficient is preferably at most 1.4 ppm / K, 1.3 ppm / K, 1.2 ppm / K, 1.1 ppm / K, 1.0 ppm / K, 0.8 ppm / K or even at most only 0.6 ppm / K.

[0019] In a preferred embodiment of the invention, the glass ceramic has a coefficient of thermal expansion of -0.8 to 0.8 ppm / K, preferably -0.5 to 0.5 ppm / K, particularly preferably -0.3 to 0.3 ppm / K. Such glass ceramics are particularly suitable for cooking surfaces in cookers with radiant or inductive heating elements.

[0020] With regard to the specific optical properties of the glass ceramic according to the invention in terms of transmittance and chromaticity, "based on a thickness of 4 mm" means that the corresponding properties are measured on a sample with a material thickness of 4 mm, or the corresponding properties are measured at different material thicknesses and converted to a material thickness of 4 mm.

[0021] The transmittance data can be converted using the Lambert-Beer law.

[0022] The transmittance τ is determined in the wavelength range of 380-780 nm using the light of the standard illuminant D65 and a 2° observer according to the preset values ​​of DIN5033. vis This value is equivalent to the brightness Y in the CIExyY color space.

[0023] Based on the L*a*b* color coordinates, the chromaticity C* is determined according to the following formula:

[0024]

[0025] The color coordinates a* and b* are determined in a known manner from the transmission spectrum of the glass ceramic using the standard light of standard illuminant D65 and a 2° observer.

[0026] Glass ceramics with a light transmittance of more than 75% relative to a thickness of 4 mm are particularly suitable for use as fireplace windows or heating panels. In fireplaces, this transmittance makes the fire particularly visible. In cookers, for example, this transmittance makes luminous displays with a relatively low luminous density (such as LCD or OLED displays) particularly visible. In this case, the light transmittance τ of the glass ceramic according to the invention is vis Preferably it is greater than 80%, particularly preferably greater than 83%, and especially preferably greater than 85%.

[0027] A chromaticity C* of less than 10 means that the color of the light changes only slightly when it passes through the glass ceramic. This is particularly important when using it as a cooking surface or fireplace viewing window, for example.

[0028] The chromaticity of the glass ceramic is particularly evident, for example, when the glass ceramic is used as a cooking surface and is provided with a white or generally light-colored bottom coating. The thickness of the glass ceramic in these applications is usually 4 mm. Therefore, the light reflected by the coating on the back side will travel a light path distance of 8 mm, so that the color shift caused by the inherent color of the glass ceramic will have a greater impact than with a shorter light path distance. Therefore, for cooking surfaces or fireplace viewing windows with a white coating on the back side, a correspondingly lower chromaticity is particularly advantageous. In this case, the chromaticity C* of the glass ceramic according to the invention is preferably less than 8, particularly preferably less than 6, most preferably less than 5.

[0029] The glass ceramics according to the present invention contain the following components (in wt%):

[0030] SiO 2 62–68,

[0031] Al 2 O 3 19–24, and

[0032] Li 2 O 2.4–3.1.

[0033] In glass ceramics, SiO 2 and Al 2 O 3 With Li 2 The O components together form the main components of the crystalline phase. At the same time, these components basically determine the glass-forming properties and the viscosity of the green glass.

[0034] SiO in the glass ceramic according to the present invention 2 The content should not exceed 68 wt% because this component will significantly increase the viscosity of the glass, especially at the processing point. 2 The content is not economical for good melting of glass and low forming temperature. Extremely high SiO content of more than 68 wt% 2 Contents may lead to the formation of keatnetite during the ceramizing process. This leads to a significant increase in the thermal expansion coefficient and a deterioration of the optical properties of the material, especially in the form of turbidity. In this case, SiO 2 The minimum content of MgO should be 62 wt% as this is advantageous for the desired properties such as chemical resistance and heat resistance.

[0035] The glass ceramic preferably contains at least 63 wt % or even 64 wt % SiO 2 . SiO in glass ceramics2 The higher the content, the better its heat resistance and chemical resistance. In addition, the glass ceramic preferably contains at most 67wt%, at most 66wt% or even only at most 65wt% SiO 2 . SiO in glass ceramics 2 The lower the content, the better the meltability and processability of the green glass in hot forming.

[0036] The Al content of the glass ceramic according to the present invention 2 O 3 The content ranges from 19 to 24 wt%. Higher Al 2 O 3 The content may cause devitrification and undesirable formation of mullite. Therefore, it should not exceed 24wt%. 2 O 3 The content is not conducive to the formation of high quartz mixed crystals and will promote the formation of undesirable crystalline phases. In addition, it is shown that lower Al 2 O 3 The content also has an adverse effect on the color of glass ceramics.

[0037] The glass ceramic preferably contains at least 20 wt %, preferably at least 21 wt % of Al 2 O 3 . Al in glass ceramics 2 O 3 The higher the content, the better its heat resistance. In addition, the glass ceramic preferably contains up to 23 wt %, particularly preferably up to 22 wt % of Al. 2 O 3 . Al in glass ceramics 2 O 3 The lower the content, the better the green glass's meltability and processability in hot forming.

[0038] The Li of the glass ceramic according to the present invention 2 The O content is in the range of 2.4-3.1 wt%. 2 O content, combined with other components within the above limits, can produce glass-ceramics with high resistance to temperature changes and good fusibility. 2 O has a great influence on the thermal expansion of glass ceramics. Therefore, Li is selected in combination with other components of the glass ceramics according to the present invention within the above-mentioned limits. 2 O, so as to achieve the temperature change resistance required by the present invention. In addition, more than 2.4wt% of Li 2The O content has a positive effect on the manufacturability of the glass ceramic, as it reduces the electrical resistance of the glass melt, lowers the viscosity and thus the processing point. By reducing the viscosity of the glass melt, the efficiency of fining can also be improved. Improved fining helps to reduce production scrap caused by bubble formation in green glass. In addition, Li 2 O also reduces the tendency of green glass to devitrify.

[0039] In a preferred embodiment, the glass-ceramic comprises at least 2.5 wt%, 2.6 wt% or even 2.7 wt% Li 2 O.

[0040] Lithium used in the manufacture of glass-ceramics is usually derived from natural mineral sources such as spodumene or petalite, or alternatively from synthetically produced Li 2 CO 3 .

[0041] In a preferred embodiment, the glass ceramic contains high quartz mixed crystals as the main crystalline phase. "Main crystalline phase" means that the high quartz mixed crystals contained in the glass ceramic are higher in volume fraction than the keatnetite mixed crystals and other crystalline phases. In one embodiment of this embodiment, the glass ceramic contains <10 vol%, preferably <5 vol%, and particularly preferably <3 vol% of keatnetite mixed crystals. Wherein, vol% refers to the volume of the glass ceramic. The volume fraction is determined by means of the Rietveld analysis method based on the X-ray diffraction spectrum.

[0042] The coefficient of thermal expansion of keatite mixed crystals is usually higher than that of high quartz mixed crystals. Therefore, a low content of keatite mixed crystals and a high content of high quartz mixed crystals are particularly advantageous for reducing the coefficient of thermal expansion of glass ceramics. In addition, a low coefficient of thermal expansion also improves the resistance of glass ceramics to temperature changes. At the same time, keatite mixed crystals, due to their generally large crystal size, cause strong light scattering, so that an excessively high keatite content has an adverse effect on the optical properties of glass ceramics. In view of this, the content of keatite in the crystalline phase should also be kept as low as possible.

[0043] In addition to the above SiO 2 、Al 2 O 3 and Li 2 In addition to the O content, the glass ceramic according to the present invention further comprises more than 2.5 wt % ZnO, preferably more than 2.6 wt %, more than 2.7 wt %, more than 2.8 wt % or more than 2.9 wt % ZnO, particularly preferably more than 3.0 wt % ZnO, and particularly preferably more than 3.2 wt % ZnO. As described above, Li 2O helps to reduce the thermal expansion coefficient of glass ceramics. Therefore, compared with the content usually used in transparent glass ceramics in the prior art, Li 2 The reduction of O content will reduce the reduction of thermal expansion coefficient of high quartz mixed crystal in glass ceramics, and thus may not reach the expansion coefficient required for cooking surface. 2 O, ZnO also contribute to lowering the thermal expansion coefficient, and thus, the Li 2 The effect of reducing O content.

[0044] In addition, ZnO will reduce the processing point and devitrification upper limit temperature of glass ceramics. 2 O 3 In combination with ZnO, the undesired formation of zinc spinel crystals may occur. Therefore, it is preferred to limit its content in the glass ceramic to a maximum of 6.0 wt.%. In addition, experience has shown that glass ceramics with very high ZnO contents are prone to the formation of undesired crystals on the surface of the glass ceramic. Therefore, it is preferred to limit the ZnO content to a maximum of 6.0 wt.%. 5.6wt%, 5.3wt%, 5.0wt%, 4.6wt%, 4.3wt%, 4.0wt% or even 3.7wt%.

[0045] In addition, excessive ZnO content will increase the refractive index difference between the crystalline phase and the residual glass phase in the glass-ceramics, which will enhance the scattering of incident light by the corresponding glass-ceramics. Therefore, the increase in ZnO content may have an adverse effect on the transmittance and chromaticity of the glass-ceramics.

[0046] To counteract this effect, the glass ceramic according to the invention also contains more than 2.5 wt % BaO. An increased BaO content reduces the tendency of the glass ceramic to scatter incident light, since the addition of BaO allows the refractive index of the residual glass phase to be matched to the refractive index of the crystalline phase of the glass ceramic at the same grain size. 2 This effect occurs when the SrO and CaO contents in the glass ceramic are simultaneously low.

[0047] In addition, similar to Li 2 O and BaO will also cause a decrease in the viscosity of the glass melt, thereby causing a decrease in the processing point. In order to improve the solubility of green glass, it is advantageous to combine the above-mentioned Li 2BaO content, the glass ceramic contains more than 2.6wt%, more than 2.7wt%, more than 2.8wt%, more than 2.9wt% or even more than 3.0wt%. In glass ceramics, BaO also plays an important role in improving the devitrification performance during the hot forming process of green glass. In this case, the content of BaO is preferably limited to less than 4.0wt%, less than 3.9wt%, less than 3.8wt%, less than 3.7wt%, less than 3.6wt%, less than 3.5wt%, less than 3.4wt%, less than 3.3wt% or even less than 3.2wt%.

[0048] Furthermore, the glass ceramic according to the invention contains more than 1.5 wt % ZrO 2 In addition, ZrO 2 It is used as a nucleating agent in glass ceramics and can react with other components of glass ceramics (such as SnO 2 and TiO 2 ) interaction. In this case, more than 1.5wt% ZrO 2 The content is beneficial to improve nucleation.

[0049] In a modified embodiment of the present invention, ZrO 2 The content of ZrO is limited to a value of 3.0 wt% because 2 The melting performance of the batch will be deteriorated. In addition, ZrO 2 Devitrification may also occur during the hot forming process. This may lead to the undesirable formation of Zr-containing crystalline phases (e.g. baddeleyite). The glass ceramic preferably contains at least >1.6 wt %, particularly preferably >1.7 wt %, and especially preferably >1.8 wt % ZrO 2 Furthermore, the glass-ceramic preferably comprises at most 2.9 wt%, 2.8 wt%, 2.6 wt%, 2.5 wt%, 2.4 wt%, 2.3 wt%, 2.2 wt%, 2.1 wt% or even only 2.0 wt% ZrO 2 With these amounts, a particularly good balance can be achieved between a positive effect on nucleation and a still acceptable deterioration in meltability and hot forming. In addition, by optimizing the ZrO 2 The content of TiO in the glass ceramics to be described later is particularly 2 In terms of content, it is also possible to achieve rapid ceramicization of green glass. Faster ceramicization under sufficient nucleation reduces the grain size in the glass ceramic, thereby reducing light scattering.

[0050] According to the present invention, 0-1 wt% of Na 2 The O content will additionally improve the solubility and devitrification properties of the glass during forming. 2O also increases the electrical conductivity of the melt. This facilitates energy coupling via the electric heating device in the melting tank. However, its content is limited because it is not incorporated into the crystalline phase, but essentially remains in the residual glass phase of the glass ceramic. When converting the crystallizable initial glass into glass ceramics, an excessively high content will impair the crystallization properties, and in particular affect the rapid ceramicization rate. As a result, in the case of preferred rapid ceramicization, the grain size in the glass ceramic can be increased, which in turn has an adverse effect on the scattering properties of the glass ceramic. In addition, a higher content will also have an adverse effect on the durability / heat resistance of the glass ceramic. Therefore, the glass ceramic preferably contains >0.1-1wt% or 0.2-0.8wt% or even 0.3-0.6wt% of Na 2 O.

[0051] In the glass ceramics according to the present invention, 0-1 wt% of K 2 The O content improves the solubility and devitrification properties of the glass during forming. 2 O can also additionally increase the electrical conductivity of the melt. This facilitates energy coupling via the electrical heating device in the melting tank. However, its content is limited because it is not incorporated into the crystalline phase, but remains essentially in the residual glass phase of the glass ceramic. When converting the crystallizable initial glass into a glass ceramic, too high a content can impair the crystallization properties, in particular the rapid ceramicization rate. 2 O, too high a ceramization speed and an increased grain size in the glass ceramic also have an adverse effect on the scattering properties of the glass ceramic. In addition, a higher content has an adverse effect on the durability / heat resistance of the glass ceramic.

[0052] If K in glass ceramics 2 O content of up to 0.8wt%, 0.6wt%, 0.5wt%, 0.4wt% or even 0.3wt%, can further improve these properties. In addition, in a special embodiment, except for unavoidable impurities, the glass ceramic does not contain K 2 O.

[0053] Furthermore, in one embodiment of the present invention, except for unavoidable impurities, the glass ceramic does not contain Cr. 2 O 3 、V 2 O 5 、MnO 2 and MoO 3 . V 2 O 5 and MoO 3 It is usually used as the primary colorant for coloring volume-colored glass ceramics, while Cr 2 O 3and MnO 2 Usually used for auxiliary coloring. The above colorants, especially V 2 O 5 Even if the amount is small, it is usually very strongly colored in the glass ceramic. Therefore, the content of the above-mentioned components in the glass ceramic according to the present invention should be kept as low as possible to ensure the transmittance and chromaticity of the glass ceramic according to the present invention. In addition, these components exist as impurities in the raw materials or as components in the blank, which are added to the batch material to improve the melting characteristics. In this case, "inevitable impurities" refers to the content of the corresponding components in the composition is less than 20ppm, particularly less than 10ppm, particularly less than 5ppm. In addition, except for inevitable impurities, the glass ceramic is preferably also free of Ce, Ni, Cu, Co, W and / or S or its oxide.

[0054] In a preferred embodiment of the present invention, the glass-ceramic contains less than 3.0 wt% TiO 2 .TiO 2 Together with ZrO 2 Together they play an important role in nucleation. 2 The content of TiO is limited to a value of up to 3.0 wt%. Larger amounts of TiO 2 It may cause devitrification during the hot forming process. In addition, it may also cause an undesirable increase in the refractive index of the residual glass phase. At the same time, the glass ceramic preferably contains at least 1wt%, 1.5wt%, 2.0wt%, >2.1wt% TiO 2 At the same time, the glass-ceramic preferably contains at most 2.7 wt%, 2.5 wt% or even only at most 2.4 wt% TiO 2 In TiO 2 At higher contents, nucleation occurs more quickly. This results in a shorter ceramizing time for the glass-ceramic. Lower contents help stabilize the ceramizing process and prevent undesired devitrification during hot forming of the green glass. In summary, TiO 2 The content of TiO has an upper limit, so as to minimize the 2 The coloring effect on the optical properties of the glass-ceramic remains low. 2 The content of ZrO should not be too low in order to still ensure sufficient nucleation and a short ceramization time. 2 The content can be reduced as another nucleating agent TiO 2 content, thereby producing glass-ceramics with reduced chromaticity.

[0055] In one embodiment of the present invention, the glass ceramic contains less than 0.05 wt % of Fe 2 O 3, preferably less than 0.04wt% Fe 2 O 3 , particularly preferably less than 0.03wt% Fe 2 O 3 , especially preferably less than 0.02wt% Fe 2 O 3 . Similar to V 2 O 5 Cr 2 O 3 、MnO 2 and MoO 3 , Fe 2 O 3 It also has a coloring effect in glass ceramics. In view of this, it is advantageous for transparent glass ceramics to 2 O 3 The content of Fe is limited to the above values. 2 O 3 Glass ceramics that are used as colorants often have a yellowing effect. For example, 2 And Fe introduced through raw material impurities 2 O 3 This may be the case with glass ceramics of the type C. If such glass ceramics are provided with a white bottom coating, for example, these bottom coatings have a clearly perceptible yellowish tint.

[0056] In addition, Fe 2 O 3 It affects not only the transmittance in the visible spectrum, but also the transmittance in the near-infrared range with a wavelength of about 3μm. 2 O 3 It not only affects the realizability of a certain color or the displayability of a color display. The absorption in the near-infrared range determines how much heat energy the glass melt can absorb in the melting tank. It determines how much heat power of the radiant heating element can pass through the glass ceramic. In addition, this absorption determines whether and which infrared sensors can be used in the cooktop. Such sensors can be designed, for example, as optical touch sensors or infrared receivers for wireless data transmission.

[0057] In this regard, it should be pointed out that in the present disclosure, the components of the glass are given in the form in which they are usually obtained by analysis. In this case, the components are usually given in a stable oxidation state (usually in the highest oxidation state). However, it should be pointed out that this does not necessarily correspond to the form in which the components actually exist.

[0058] For example, iron in oxide glass can exist in divalent and trivalent forms, namely as Fe 2+ or FeO or as Fe 3+ or Fe2 O 3 In the present disclosure, the data on the content of the corresponding component are related to the usual analytical data, however, it is obvious that this component may also be present in a form that deviates from the usually given "ideal" oxidation state.

[0059] In one embodiment of the present invention, the glass ceramic contains less than 1.2 wt %, preferably less than 1.0 wt %, particularly preferably less than 0.8 wt %, less than 0.7 wt %, less than 0.6 wt %, and particularly preferably less than 0.5 wt % of MgO. MgO has a positive effect on the solubility and devitrification properties of the glass ceramic, but a too high content increases the color of the glass ceramic and increases the thermal expansion coefficient of the high quartz mixed crystal phase. Therefore, it has been found to be advantageous for colorless and transparent glass ceramics to limit the MgO content to the above limit values.

[0060] Furthermore, according to another embodiment of the invention, the transparent lithium aluminum silicate glass ceramic contains less than 1.2 wt %, preferably less than 1.0 wt %, particularly preferably less than 0.8 wt %, and particularly preferably less than 0.5 wt % of CaO. CaO has a favorable effect on the devitrification properties of the glass ceramic. However, it has proven to be advantageous for colorless and transparent glass ceramics to limit the CaO content to the above values, since CaO contributes to increasing the grain size in the glass ceramic. The increase in grain size in turn leads to increased scattering, which results in a deterioration in the optical properties of the glass ceramic.

[0061] In a further development of the invention, the glass ceramic contains less than 0.2 wt %, preferably less than 0.15 wt %, particularly preferably less than 0.1 wt % SnO 2 SnO 2 Assists in clarifying green glass. 2 Glass ceramics with a content of SnO are characterized by particularly few defects caused by the included bubbles. 2 In combination with other components of the glass ceramic according to the invention, the nucleation is additionally positively influenced. However, this content should not exceed 0.2 wt %, since SnO 2 This can have an adverse effect on the optical properties of the glass ceramic and may in particular lead to an increase in the chromaticity of the glass ceramic. In addition, higher SnO 2 The content may also cause undesired crystallization of Sn-containing crystalline phases (such as cassiterite) on contact materials (such as Pt / Rh) during the molding process, thereby further deteriorating the optical properties of the glass-ceramic.

[0062] In order to assist in the clarification of green glass, in addition to the above SnO 2 In addition to the content, it may also contain no more than 2wt% of As2 O 3 and / or Sb 2 O 3 In this case, it has proven to be advantageous to reduce SnO content as much as possible. 2 Because as mentioned above, SnO 2 In addition to its positive effect on the clarification of green glass, it also has a negative impact on the optical properties of the glass ceramic. The reason for this is that SnO 2 May be related to TiO 2 Together, they form an additional absorption band for the incident light, causing a red shift in the transmitted light. 2 Helps increase Fe 2 O 3 Medium Fe 2+ content, thereby combining TiO 2 And enhance the coloring.

[0063] As 2 O 3 and Sb 2 O 3 Basically, they have the same effect and can be contained in the glass ceramic alone or in combination. In all cases, this content should preferably not exceed 2 wt%. 2 O 3 and / or Sb 2 O 3 " means that these two components can be contained in the glass ceramic in corresponding contents alone or in combination.

[0064] Accordingly, according to another embodiment of the present invention, except for unavoidable impurities, the glass ceramic does not contain SnO 2 and contains 0.5wt% to 1.5wt% of As 2 O 3 and / or Sb 2 O 3 This clarification is completely free of SnO 2 and thus avoids SnO 2 The above-mentioned influence on the optical properties of glass ceramics is particularly beneficial for producing transparent and color-neutral glass ceramics. 2 Different, As 2 O 3 and Sb 2 O 3 Will not affect the color of glass ceramics because of its Fe 2 O 3 The reduction effect is not like SnO 2 So strong, and will not bind TiO 2 This results in enhanced coloring.

[0065] Furthermore, in one embodiment of the present invention, it is provided that the transparent lithium aluminosilicate glass ceramic contains 0.01-0.07 wt % of Nd 2 O 3 , preferably 0.03-0.06wt% Nd 2 O 3 In this case, especially with the help of SnO 2 When clarifying, Nd 2 O 3 Helps to compensate for SnO 2 In this case, especially in SnO 2 When the content exceeds 0.1wt%, Nd is added 2 O 3 This is advantageous for producing glass ceramics that are as neutral in color as possible.

[0066] Fe within the above limits 2 O 3 and TiO 2 In glass ceramics with high content, Nd is added 2 O 3 It also helps to reduce or eliminate the 2 O 3 and TiO 2 This effect is based on the yellowing caused by Nd at wavelengths of 513, 526, 575, 585 and 745nm. 2 O 3 Narrow absorption bands in the visible spectral range are particularly advantageous for the production of transparent, color-neutral glass ceramics.

[0067] In summary, the clarification of glass ceramics can be achieved by adding SnO 2 , by making SnO 2 With As 2 O 3 and / or Sb 2 O 3 combination, or by using a SnO-free 2 In the case of As 2 O 3 and / or Sb 2 O 3 For clarification.

[0068] In one embodiment of the present invention, the glass ceramic comprises the following components (based on oxides, wt %):

[0069]

[0070]

[0071] Furthermore, such glass ceramics may also contain SrO, wherein the SrO content mainly comes from impurities in the raw materials used to produce the glass ceramic. Among other things, SrO contributes to the scattering of light by the glass ceramic. Therefore, it is advantageous to keep the SrO content in the glass ceramic as low as possible.

[0072] The following table contains three further embodiments of the composition of the glass ceramic according to the invention comprising the following components (based on oxides, in wt %):

[0073] Preferred Particularly preferred The most preferred <![CDATA[Si 2 The]]> 62–67 63–66 64–66 <![CDATA[Al 2 THE 3 ]]> 19–22 19–22 19–22 <![CDATA[Li 2 The]]> 2.5–3.0 2.6–2.9 2.6–2.8 <![CDATA[Na 2 The]]> 0.1–0.8 0.2–0.7 0.3–0.6 <![CDATA[K 2 The]]> <0.8 <0.4 <0.1 MgO 0–0.7 0–0.6 0.1–0.6 CaO <1.0 <0.5 <0.1 BaO >2.5 2.5–4.5 2.5–4.0 ZnO >2.5 2.6–4.0 2.7–3.7 <![CDATA[TiO 2 ]]> 1.5–2.7 2.0–2.5 2.1–2.4 <![CDATA[ZrO 2 ]]> 1.5–3.0 1.6–2.8 1.6–2.0

[0074] Except for inevitable impurities, the above composition may not contain K 2 O.

[0075] Three alternative embodiments of the composition of the glass ceramic according to the present invention comprise the following components (based on oxides, in wt %):

[0076]

[0077]

[0078] Further embodiments of the composition of the glass ceramic according to the invention are given below (based on oxides, in wt %):

[0079] Preferred Particularly preferred The most preferred <![CDATA[Si 2 The]]> 62–67 63–66 63.5–65.5 <![CDATA[Al 2 THE 3 ]]> 19–22 20–22 20.5–21.5 <![CDATA[Li 2 The]]> 2.4–3.1 2.4–3.1 2.4–3.1 <![CDATA[Na 2 The]]> 0.1–0.8 0.15–0.6 0.2–0.45 <![CDATA[K 2 The]]> 0.1–0.8 0.1–0.6 0.15–0.6 MgO 0–0.7 0–0.5 >0–0.45 CaO 0–1.0 0.4–1.0 0.8–1.0 BaO >2.5 >2.5–3.2 >2.5–2.7 ZnO >2.5 2.6–3.5 >2.6–3.4 <![CDATA[TiO 2 ]]> 1.0–2.7 1.5–2.5 2.0–2.4 <![CDATA[ZrO 2 ]]> 1.5–3.0 1.6–2.8 1.6–2.0

[0080] In addition to the components known specifically from the above compositions, the corresponding glass ceramics may also comprise further components, in particular fining agents.

[0081] Based on the above composition, SnO 2 , by making SnO 2 With As 2 O 3 and / or Sb 2 O 3 Combination or in the absence of SnO 2 In the case of only As 2 O 3 and / or Sb 2 O 3 In this case, the above-mentioned limit values ​​can be applied with respect to the content of the corresponding components in the composition.

[0082] Furthermore, in a preferred embodiment of the present invention, the grain size of the transparent lithium aluminum silicate glass ceramic in the high quartz mixed crystal phase is less than 80 nm, preferably less than 70 nm, particularly preferably less than 60 nm, and particularly preferably less than 50 nm. The grain size directly affects the optical properties of the glass ceramic. An excessively large grain size leads to enhanced light scattering in the glass ceramic, which manifests itself as turbidity in the glass ceramic.

[0083] According to another embodiment of the present invention, Al 2 O 3 With TiO 2 The ratio of Al is in the range of 7 to 12, preferably in the range of 8 to 11, and particularly preferably in the range of 8.5 to 10.5. 2 O 3 With TiO 2 Ratios within this range have a particularly favorable effect on the color of the glass ceramic and at the same time enable particularly stable ceramicization.

[0084] The glass ceramics according to the invention are used as cooking surfaces, fireplace windows, grilling or frying surfaces, covers for fuel elements in gas grills, oven windows, in particular oven windows for pyrolysis ovens, work surfaces or tabletops in kitchens or laboratories, covers for lighting devices, in fire-resistant sealing glasses and as safety glass, optionally in laminated composites, as carrier plates or oven linings in thermal processes or as back covers for mobile electronic devices.

[0085] The glass ceramic according to the invention can be used in particular as a cooking surface. This cooking surface can be provided completely or partially with a decorative or functional coating on the top and / or bottom. A touch sensor for operating the cooking surface can also be provided on the bottom. This can be, for example, a capacitive sensor that is embossed, glued or pressed.

[0086] The present invention will be further described below in conjunction with the embodiments. DETAILED DESCRIPTION

[0087] The crystallizable green glass in the example was melted from a technical batch raw material commonly used in the glass industry at a temperature of 1680° C. for 4 hours. The requirements for economical raw materials and low impurity content of undesirable impurities can be reconciled by selecting this raw material. After the mixture has been melted in a crucible made of sintered quartz glass, the melt is transferred to a Pt / Rh crucible with an inner crucible made of quartz glass and homogenized for 60 minutes at a temperature of 1640° C. by stirring. After homogenization, the glass is clarified at a temperature of 1680° C. for 3.5 hours. Subsequently, a 120×120×30 mm glass casting is performed. 3The blocks are then cooled in an annealing furnace starting at 650-670°C at 30 K / h to room temperature, depending on the viscosity of the glass, in order to relieve the stresses. These castings are divided into the required sizes for testing and ceramization.

[0088] The green glass sample was ceramized by means of a ceramization process having the following steps:

[0089] a) Heating from room temperature to 740°C within 25 minutes,

[0090] b) maintained at 740°C for 20 minutes,

[0091] c) increasing the temperature from 740°C to 780°C within 6.5 minutes,

[0092] d) Raise the temperature from 780°C to 825°C within 20 minutes,

[0093] e) increasing the temperature from 825°C to 910°C within 8.5 minutes,

[0094] f) maintaining the temperature at 910°C for 10 minutes,

[0095] g) Cool to room temperature over 125 minutes.

[0096] This ceramization process can be considered as exemplary. The properties of the glass-ceramic can be fine-tuned by varying the temperature and holding time of the individual steps or by adding other steps (eg additional holding time).

[0097] For example, the following parameters can also be used for ceramicization:

[0098] a) heating from room temperature to 680°C to 760°C within 3 to 60 minutes,

[0099] b) heating the crystallizable green glass to a nucleation temperature range T for a period of 10 to 100 minutes a to 800°C,

[0100] c) heating the glass containing the crystal nuclei to a temperature range of 810° C. to 930° C. with a high crystal growth rate within 5 to 80 minutes,

[0101] d) maintaining the temperature at 810° C. to 930° C. for 2 to 60 minutes,

[0102] e) Cool to room temperature in less than 150 minutes.

[0103] The following table contains compositions and material properties of examples according to the present invention.

[0104] In this case, the coefficient of thermal expansion CTE is determined by means of a method which is essentially based on DIN ISO 7991 from 1998.

[0105] To measure the upper devitrification temperature (OEG), green glass is melted in a Pt / Rh 10 crucible. The crucible is then kept for 5 hours at different temperatures within the processing temperature range. The upper temperature at which the first crystals appear at the contact surface between the glass melt and the crucible wall determines the OEG value.

[0106] The processing point (T) of green glass was determined using a stirred viscometer according to DIN ISO 7884-2. 4 ).

[0107] When converting green glass into glass ceramic, the density increases, since the density of the crystalline phase is higher than that of the amorphous glass. The so-called shrinkage represents the linear length change during the conversion of green glass into glass ceramic. This shrinkage is calculated (in percent) from the density of the green glass and the density of the glass ceramic using the following formula:

[0108]

[0109] Among them, T g Indicates the transition temperature of green glass, also known as the glass transition temperature. This transition temperature is determined by dilatometry.

[0110] The transmittance τ is determined in the wavelength range 380-780 nm using the light of the standard illuminant D65 and a 2° observer according to the preset values ​​of DIN 5033. vis This value is equivalent to the brightness Y in the CIExyY color space. This value is a measure of the human eye's perception of brightness.

[0111] The transmission spectra were determined according to ISO 15368: 2021. Table 2 exemplarily contains the spectral transmittances "T@..." for wavelengths of 470 nm, 600 nm, 630 nm, 700 nm, 950 nm and 1600 nm.

[0112] The color coordinates in the CIExyY color space and in the CIELab color space were determined in transmission using a 2° observer and the light of standard illuminant D65 according to the specifications of CIE 1932.

[0113] All transmittance measurements were performed on samples with a thickness of 4 mm and smoothed on both sides.

[0114] The volume fraction “HQMK phase content” and the grain size of the crystalline phase “HQMK grain size” were determined from the X-ray diffraction spectrum by means of Rietveld analysis.

[0115] Table 1: Compositions of exemplary glass-ceramics, in wt % based on oxides

[0116]

[0117]

[0118] Table 1

[0119] Example 8 9 10 11 12 13 14 <![CDATA[SiO 2 ]]> 63.900 62.500 65.900 64.500 64.200 64.200 64.900 <![CDATA[Al 2 THE 3 ]]> 21.080 23.200 19.920 21.060 21.940 21.950 21.310 <![CDATA[Li 2 The]]> 3.020 2.470 2.740 3.070 2.740 2.710 2.690 <![CDATA[Na 2 The]]> 0.303 0.291 0.336 0.306 0.507 0.506 0.503 <![CDATA[K 2 The]]> 0.227 0.321 0.230 MgO 0.377 0.074 0.136 0.365 0.516 0.140 0.140 CaO 0.432 0.940 0.013 0.434 0.020 0.012 0.012 SrO 0.017 0.014 0.020 0.017 0.014 0.016 0.014 BaO 3.020 2.570 3.770 3.050 2.620 3.010 2.640 ZnO 2.700 3.410 2.830 2.700 3.110 3.090 3.470 <![CDATA[TiO 2 ]]> 2.222 2.228 2.352 2.231 2.340 2.335 2.350 <![CDATA[ZrO 2 ]]> 1.830 1.850 1.840 1.850 1.830 1.830 1.830 <![CDATA[P 2 THE 5 ]]> <![CDATA[As 2 THE 3 ]]> 0.830 <![CDATA[SnO 2 ]]> 0.101 0.106 0.103 0.112 0.113 0.109 <![CDATA[Fe 2 THE 3 ]]> 0.014 0.014 0.015 0.014 0.014 0.015 0.014 <![CDATA[Nd 2 THE 3 ]]> 0.051 <![CDATA[MnO 2 ]]> <![CDATA[HfO 2 ]]> 0.032 0.032 0.033 0.033 0.032 0.032 0.032

[0120] Table 2: Material properties of exemplary glass-ceramics

[0121] Example 1 2 3 4 5 6 <![CDATA[T g ]]> ℃ 685 685 678 680 686 689 Glass density <![CDATA[g / cm 3 ]]> 2.5121 2.5143 2.5106 2.5267 2.5174 2.5036 <![CDATA[T 4 ]]> ℃ 1305 1307 1328 OEG ℃ 1275 1285 1315 HQMK phase content Vol.-% 62 59 59 57 54 61 HQMK grain size nm 47 41 47 53 42 36 Density of glass ceramics <![CDATA[g / cm 3 ]]> 2.5759 2.5796 2.5779 2.5872 2.5815 2.5820 Shrinkage % 0.833 0.851 0.878 0.786 0.835 1.023 CTE(20;700℃) ppm / K 0.16 0.12 0.15 0.26 0.31 -0.26 <![CDATA[τ vis ]]> % 85.2 86.3 83.9 80.9 84.6 85.9 L* 94.0 94.4 93.4 92.1 93.7 94.3 a* -0.1 -0.2 -0.2 -0.2 0.0 -0.3 b* 5.0 4.6 6.3 8.9 5.1 4.9 C* 5.0 4.6 6.3 8.9 5.1 4.9 T@400nm % 67.4 69.0 60.8 52.8 69.5 67.0 T@470nm % 80.4 81.9 78.0 72.7 79.5 81.2 T@600nm % 87.1 88.0 86.3 84.2 86.7 87.6 T@630nm % 87.9 88.7 87.4 85.6 87.6 88.3 T@700nm % 89.2 89.9 88.9 87.8 89.0 89.5 T@950nm % 90.0 90.1 89.7 89.4 89.5 89.9 T@1600nm % 89.3 89.3 89.2 89.2 89.0 89.1

[0122] Table 2

[0123]

[0124]

[0125] Table 2

[0126]

[0127]

Claims

1. A transparent lithium aluminosilicate glass ceramic having a thermal expansion coefficient of -0.8 to 1.5 ppm / K in the range of 20° C. to 700° C., Based on a thickness of 4 mm, the light transmittance τ of the glass ceramic is vis More than 75%, and based on a thickness of 4 mm, the chromaticity C* of the glass-ceramic is less than 10, the glass-ceramic comprising the following components based on oxides in wt%:

2. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that Except for inevitable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

3. The transparent lithium aluminum silicate glass ceramic according to claim 1 or 2, characterized in that: The transparent lithium aluminosilicate glass ceramic contains less than 3.0 wt %, preferably less than 2.7 wt %, particularly preferably less than 2.5 wt %, and especially preferably less than 2.4 wt % of TiO 2 .

4. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 0.05 wt %, preferably less than 0.04 wt %, particularly preferably less than 0.03 wt %, and especially preferably less than 0.02 wt % of Fe 2 O 3 .

5. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 1.2 wt %, preferably less than 1.0 wt %, particularly preferably less than 0.8 wt %, especially preferably less than 0.5 wt % of MgO.

6. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 1.2 wt %, preferably less than 1.0 wt %, particularly preferably less than 0.8 wt %, especially preferably less than 0.5 wt % of CaO.

7. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 0.2 wt %, preferably less than 0.15 wt %, particularly preferably less than 0.1 wt % SnO 2 .

8. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that Except for unavoidable impurities, the transparent lithium aluminosilicate glass ceramic does not contain SnO 2 and contains 0.5 wt % to 1.5 wt % of As 2 O 3 and / or Sb 2 O 3 .

9. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains 0.01-0.07 wt % of Nd2O3.

10. The transparent lithium aluminum silicate glass ceramic according to claim 7 or 8, characterized in that: The transparent lithium aluminosilicate glass ceramic comprises the following components based on oxides in wt %:

11. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The grain size of the transparent lithium aluminum silicate glass ceramic in the high quartz mixed crystal phase is less than 80 nm.

12. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The ratio of Al2O3 to TiO2 is in the range of 7 to 12, preferably in the range of 8 to 11, particularly preferably in the range of 8.5 to 10.

5.

13. Use of the glass ceramic according to any of the preceding claims as a cooking surface, a fireplace viewing window, a grilling or frying surface, a cover for a fuel element in a gas grill, an oven viewing window, in particular an oven viewing window for a pyrolysis oven, a work surface or tabletop in a kitchen or laboratory, a cover for a lighting device, in fire-resistant sealing glass and as safety glass, optionally in a laminated composite, as a carrier plate or furnace lining in thermal processes or as a back cover for mobile electronic devices.

Citation Information

Patent Citations

  • Lithium aluminum silicate glass ceramic

    DE202022106826U1

  • Glass ceramic with reduced lithium content

    EP3502069A1

  • Partially crystallised glass plate

    US20170050880A1

  • Beta-quartz glass-ceramics with high zinc content

    US20200140322A1

  • Transparent beta-quartz glass-ceramics with low lithium content

    US20200189965A1